IMPROVING STUDENTS’ VOCABULARY ACHIEVEMENT BY USING STORYTELLING - Novalina Sembiring; Fiber Y.A. Ginting (JURNAL LINER (Language Intelligence and Educational Research), 2019)
This study was aimed to improve the students’ vocabulary achievement by using storytelling. It was conducted at SMP Negeri 22 Medan, with grade eighth students as the subject of the study. This study was conducted by applying Classrom Action Research (CAR), which consisted of two cycles and each cycle consisted of three meetings. The instruments of collecting data were vocabulary test, observation checklist and fieldnotes. The data analysis showed that story telling can improve students’ vocabulary achievement from pre test17,51 to 25 in formative test and to 64 inpost test. The percentage of the students’ score also improvefrom the pre-test to formative test 43,34% and from pre-test to post-test is 265%. Furthermore, the result of observation checklist and fieldnotes showed that the students were interested in teaching and learning English by using storytelling. These indicated that there was a significant improvement of the students’ vocabularyachivement by using storytelling.